Virulence of brown planthopper (Nilaparvata lugens) populations from South and South East Asia against resistant rice varieties. (December 2015) - Horgan, Finbarr G.; Ramal, Angelee Fame; Bentur, Jagadish S.; Kumar, Ram; Bhanu, K. Vasanta; Sarao, Preetinder Singh; Iswanto, Eko Hari; Van Chien, Ho; Phyu, Moe Hnin; Bernal, Carmencita C.; Almazan, Maria Liberty P.; Alam, Mohammad Zahangeer; et al.
Abstract: This study examines the utility of resistant varieties and their associated resistance genes against brown planthopper, Nilaparvata lugens (Stål), populations from South and South East Asia. A collection of 39 rice accessions that included resistant, tolerant and susceptible varieties and breeding lines were examined for performance against populations of N. lugens from India (4), Bangladesh (1), Myanmar (1), Vietnam (1), Indonesia (1), China (1), Taiwan (1), and the Philippines (2). Planthopper virulence varied between regions; however only 6 varieties were generally less damaged than the susceptible check Taichung Native 1 (TN1) among ≥50% of the test populations. Each of these 6 varieties contained multiple resistance genes. One further variety, also with multiple resistance genes, and a modern cultivar (possibly with the Bph3 gene) were moderately effective against the South Asian populations, whereas a traditional variety with the Bph6 gene was effective against South East Asian populations. Bph1, bph2, bph5, bph7, bph8, Bph9, Bph10 and Bph18 were ineffective against most planthopper populations. Bph20, Bph21, and Bph17 have potential to be used in resistance breeding in both South and South East Asia, whereas BPH25 and BPH26 have potential for use in South Asia. The results indicate that only a few of the currently available resistance genes will be effective in monogenic rice lines; but that pyramiding of two or more genes with strong to weak resistance could improve resistance strength and durability as apparent with the most resistant, traditional varieties. Strategies to avoid planthopper adaptation to resistant rice varieties are discussed. Highlights: Thirty nine rice varieties including known resistance donors were tested against twelve Nilaparvata lugens populations. The varieties were evaluated using replicated seedbox tests at rice research centers in eight Asian countries. Six varieties from South Asia were consistently resistant to populations in the study. Many varieties had only weak resistance against the planthopper including some with known resistance genes. Virulence of N. lugens on a few varieties differed between South and South East Asia.